A study of the students awareness about the 1Malaysia concept / Mohammad Ariff Haron and Shamsul Safri Samsudin - Haron, Mohammad Ariff; Samsudin, Shamsul Safri (Faculty of Administrative Science and Policy Studies, 2012)
1Malaysia or 'One Malaysia' is a continuation of the concept by previous prime minister, aimed to develop the country as a developed country. The 1Malaysia concept were introduced in 2009 by Dato’ Seri NajibTun Abdul Razak in order to achieve the developed country. The study examines the student’s awareness about the 1Malaysia concept. This study are focused the factors contribute to the student’s awareness about 1Malaysia concept among the final semester students of Bachelor in Administrative Science, to determine the significant relationships between factors and 1Malaysia concept, and to identify the most influential factors that influence student’s awareness. A convenient sampling of 86 students of Faculty of Administrative Science and Policy studies in UiTM Malacca City Campus. The finding of this study found that , it can be summarize that all four factors which are mass media, knowledge, personal attitudes and government are contribute towards the student’s awareness about the 1Malaysia concept. It can be concluded that the entire hypothesis is achieved and we can concluded by referring the most influenced factor that lead to the student’s awareness is knowledge, personal attitude and government programs.